Helianthus annuus assisted green synthesis of Co3O4 and Ag‐Co3O4 and evaluation of their catalytic activities toward photodegradation of crystal violet dye. Issue 4 (7th January 2021) - Saeed, Muhammad; Haq, Atta Ul; Muneer, Majid; Usman, Muhammad; Naqvi, Syed Ali Raza; Adeel, Muhammad; Nisar, Asif
Abstract: Nowadays, plants assisted green synthesis of metal oxide nanoparticles attracted the interest of researchers due to economic and environmental points of view. This article reports the Helianthus annuus (sunflower) leaves assisted green synthesis of Co3 O4 and Ag‐Co3 O4 particles. In this method, the leaves extract of Helianthus annuus (sunflower) is utilized as a reducing and stabilizing agent for the synthesis of Co3 O4 and Ag‐Co3 O4 particles. XRD and FTIR confirmed the crystalline and spinel phase of prepared Co3 O4 and Ag‐Co3 O4 particles. The catalytic activities of prepared particles were evaluated over the photodegradation of crystal violet dye under visible irradiation. About 63% and 98% of 100 mg/L degraded over 0.002 g/ml of Co3 O4 and Ag‐Co3 O4, respectively. The reaction kinetics and mechanism were described in terms of the Eley‐Rideal mechanism. The rate constant was determined as 0.0075 and 0.0167 per minute for Co3 O4 and Ag‐Co3 O4, respectively.